The Effectiveness of Occupational Therapy : Drawing on Mrs. “K” on The Ability to Control Auditory Hallucinations in The Flamboyant Room Dr. RSJ. Radjiman Wediodiningrat Lawang - Nanda Leoni Agustin; Enggal Hadi Kurniyawan; Amalia Kusumaningsih; Fitrio Deviantony (Universitas Bondowoso, 2022)
Introduction: Hallucinations are defined as perceptual disturbances in which an object is not stimulated from outside, this sensory perception disorder covers all five senses. One effort that can be done to overcome hallucination is by occupational drawing therapy. Drawing therapy can release the patient’s emotions, express themselves through non-verbal ways and build communication. This final scientific paper aims to determine the drawing strategy for reducing hearing hallucination symptoms. Method: The research design uses a qualitative case study. This case study explores a problem in patients with sensory percepyion disorders: auditory hallucination with a sample of 1 person. Result: After 3 days of drawing therapy, there were changes in the symptoms that appeared in Mrs. “K” before and after being given the intervention of occupational therapy drawing, where before being given therapeutic therapy there were 12 symptoms (85%) from 14 symptoms and after the intervention was given 3 symptoms (22%).Therapy can minimize the patient’s interaction with his own world, remove thoughts, feeling, or emotions that have been influencing, unconscious behavior, motivate and provide joy, entertainment, and attention to the mind from hallucinations so that the mind does not focus on the hallucinations. Conclusion: Drawing therapy is effective in reducing auditory therapy is effective in reducing auditory symptoms in schizophrenic patients.